2015
DOI: 10.5171/2015.709531
|View full text |Cite
|
Sign up to set email alerts
|

Does Service Failure Context Matter? Customers’ Response to Service Recovery

Abstract: Because service failures are difficult to avoid in the services context due to their characteristics, firms need to offer an adequate service recovery to compensate customers. Customer behavior may be affected either by the failure or its recovery. The purpose of this study is to explore the impact of service failure severity in customers' post-recovery behavior. The study comprises a sample of 40,813 customers, representing customers who had experienced a problem with the service provider and customers who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Evidence from this study showed that PSSF had positively influenced customer NWoM regardless of airline carrier. This finding is in line with the results of a number of previous studies (McColl-Kennedy et al, 2003;Soares and Proenc ¸a, 2015), especially those of Yildirim et al (2018) who likewise found that dissatisfied customers would engage in NWoM after an initial service failure.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…Evidence from this study showed that PSSF had positively influenced customer NWoM regardless of airline carrier. This finding is in line with the results of a number of previous studies (McColl-Kennedy et al, 2003;Soares and Proenc ¸a, 2015), especially those of Yildirim et al (2018) who likewise found that dissatisfied customers would engage in NWoM after an initial service failure.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…Numerous studies have highlighted the effect of PSSF on various service failure outcomes, such as loss of customer loyalty and reduced re-purchase intention (Li, 2015). Soares and Proenc ¸a (2015) reported that service failures had had a strong negative impact on a firm's relationship with its customers. In this regard, Ozuem et al (2021) showed that SRSs are critical in reducing customer desire to switch to alternative service providers.…”
Section: Perceived Severity Of Service Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Gronroos suggested that service providers take some action after service failure as consumer's expectation related to the services does not match the delivered (Grönroos, 2007;Harrison-Walker, 2019a).The paradox of service recovery has importance with the condition that the customer becomes more satisfied after service recovery than those who have not such failure experience (Soares & Proença, 2015;Yunus, 2023).Previous studies suggested that after service failure, customers have feelings of injustice and they expect to restore the feelings of justice (Suri et al, 2019). The service failure which may cause cost or material damage to the customer might increase the need for recovery strategies like empathy and continuous concern whereas for the customer who responds to emotions like anger immediate correction and apologies recovery strategies can be adopted (Bakar et al, 2019).…”
Section: Service Recovery Strategiesmentioning
confidence: 99%
“…In an earlier study by Smith et al (1999), it was stated that the service failure severity significantly affects the impression the consumers have toward the service provider. Besides, it will also trigger unfavorable behavioral actions such as consumer complaints, negative word-of-mouth (WOM), and service termination or switching to other service providers (Soares & Proença, 2015). In addition, the severity of service failure will also have adverse effects on business outcomes, such as loss of customers and a decrease in revenue (Keiningham et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%